Targeting mitochondrial homeostasis in the treatment of non-alcoholic fatty liver disease: a review - Deng, Yalan; Dong, Yuan; Zhang, Sitian; Feng, Yingmei (Frontiers in Pharmacology, 2024)
Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease worldwide, and its prevalence is rapidly increasing. Antioxidants, lipidlowering medications, and lifestyle interventions are the most commonly used treatment options for NAFLD, but their efficacy in inhibiting steatosis progression is limited and their long-term ineffectiveness and adverse effects have been widely reported. Therefore, it is important to gain a deeper understanding of the pathogenesis of NAFLD and to identify more effective therapeutic approaches. Mitochondrial homeostasis governs cellular redox biology, lipid metabolism, and cell death, all of which are crucial to control hepatic function. Recent findings have indicated that disruption of mitochondrial homeostasis occurs in the early stage of NAFLD and mitochondrial dysfunction reinforces disease progression. In this review, we summarize the physical roles of the mitochondria and describe their response and dysfunction in the context of NAFLD. We also discuss the drug targets associated with the mitochondria that are currently in the clinical trial phase of exploration. From our findings, we hope that the mitochondria may be a promising therapeutic target for the treatment of NAFLD.